Ways of thinking of eastern peoples - "Nakamura, Hajime" (Japan, 1960)
Ways of thinking of Eastern people is a comparative study of ways of thinking of major peoples of Asia. It has been widely admitted that this is the first attempt to give a survey and analysis of ways of thinking of Asians, which differ with peoples. The author has chiefly centered in pointing out features of Indian ways of thinking, as well as Chinese, Japanese and Tibetian ones.
Keywords: Thought and thinking